Parental Goals for Adolescents - McNamara, Juliette Lauren (Wake Forest University, 2010)
Parental goals reflect parents' desires for particular outcomes in their child's development. Parental goals might be one force that motivates parenting practices and shapes a child's development through adolescence (Chao, 1995; Eccles, 1992). For this reason and because there is lack of past research that has addressed this topic, this study was designed to examine parental goals for adolescents. Specifically, I examined mothers' short-term goals (i.e., goals for the adolescent period) in two domains especially relevant to adolescents: risk-taking and parent-child relationships. Thirty-six mothers of adolescents (range 11-18 years of age) from three ethnic groups (non-Hispanic White, African American, and Hispanic/Latino) participated. Within each ethnic group, mothers from three socioeconomic groups (less than $40,000; between $40,000 and $80,000; greater than $80,000) were represented. Data were collected via in-depth semi-structured interviews, as well as a small number of closed-ended scaled questions concerning the importance of specific goals. Descriptive information for scaled questions by ethnicity and economic status is provided. Qualitative analyses were used to extract themes concerning mothers' goals from the open-ended questions. Results suggest that there were both similarities and differences in mothers' goals for their adolescents in the domains of risk-taking and parent-adolescent relations. Recommendations for future research are discussed.
Keywords: adolescents; goals; parent-child relations; parenting; risk-taking